E-Learning System's Acceptance : A Comparative Study - Abu-Shanab, Emad (International Journal of Web-Based Learning and Teaching Technologies, 2014)
The major limitation for adopting e-learning systems is students and teachers perceptions of such applications. EduWave is a system implemented in Jordan, to be used by teachers, students and other stakeholders in public schools in the country. This study tried to contrast the perceptions of students and teachers and conclude to future agenda for improving the success chances of such systems. The research utilized results from two empirical studies, with 2 surveys applied to both teachers and students to probe their opinions regarding the obstacles facing EduWave utilization, the advantages and disadvantages of the system, the functionalities used, and the factors influencing the adoption. Results supported the original Technology Acceptance Model (TAM), with significant prediction of intentions to use EduWave through perceived usefulness and perceived ease of use for both teachers and students. Also, teachers and students results did not support the role of trust in the process. Conclusions and future work are stated at the end.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuNDAxOC9pandsdHQuMjAxNDEwMDEwMQ